Clinical patterns and risk factors of vulvo-vaginal candidiasis among women of reproductive age attending a tertiary hospital in central India - Siddiqui, Rafat (Stamford Journal of Microbiology, 2020)
Vulvo-vaginal Candidiasis (VVC) is the most common fungal infection in women of reproductive age. Data related to distribution and risk factors are very limited in India. This study was designed to observe the prevalence of VVC among women of reproductive age group, find the species of Candida causing such infection and find the risk factors associated with VVC. All female patients in the childbearing age group, fulfilling the clinical criteria of vaginitis, reported between January 2016 and June 2017 were included in this study. Standard procedures were followed to collect vaginal swabs. Culture and microscopic examinations were done to isolate Candida albicans and non-albicans Candida (NAC) from the specimens. Descriptive and analytic statistics was used to illustrate the basic and disease characteristics of the study participants. The odds-ratio (OR) associated with each potential risk factor at 95% confidence interval (CI) were calculated. All results were considered significant at P<0.05. Out of total 168 subjects, 32.7% showed pure growth of Candida species and NAC species were found to be predominant (65.4%) followed by C. albicans (34.6%). Maximum Candida positivity was found in age group 21-30 years (60%) compared to other age groups (P<0.05). Candida positivity was found to be higher among pregnant (45.0%) than non-pregnant (28.9%) women (P<0.05) suggests that pregnant women are twice at odds for developing VVC as compared to non-pregnant women. The higher positivity in patients of vaginal discharge with pruritus was found to be statistically significant (P<0.05). One in three patients was found to be positive for VVC and NAC was more prevalent as compared to candida albicans. This study concluded that pregnant women are at risk for VVC. Stamford Journal of Microbiology, Vol.9(1) 2019: 27-31